Diagnostic and Immunologic Testing for Varicella in the Era of High-Impact Varicella Vaccination: An Evolving Problem . (21st October 2022) - Dollard, Sheila; Chen, Min-hsin; Lindstrom, Stephen; Marin, Mona; Rota, Paul A
Abstract: The clinical presentation of varicella in unvaccinated persons, with skin vesicles and scabs, has facilitated the use of rapid diagnostic methods for confirming disease. Polymerase chain reaction (PCR) assays are the diagnostic method of choice. The sharp decline in unmodified cases of varicella due to the US varicella vaccination program has led to fewer healthcare providers being familiar with varicella presentation and an increased reliance on laboratory diagnosis to confirm suspected cases. The mild, atypical presentation of the disease in vaccinated persons (fewer skin lesions, mostly maculopapular) has made it more challenging for providers to recognize and also to collect samples to detect the virus. Nonetheless, PCR is highly sensitive and specific in confirming modified disease if adequate samples are provided. While a positive PCR result is confirmatory, interpreting a negative result can prove to be more challenging in determining whether suspected varicella is falsely negative or attributable to other causes. Enhanced education of healthcare providers is critical for adequate specimen collection from modified varicella cases. In addition, more sensitive commercial serologic assays are needed in the United States for varicella immunity testing in the vaccine era.